Introduction: Telling the Story of MIT Economics in the Postwar Period - E. Roy Weintraub (Duke University, Center for the History of Political Economy (CHOPE), 2014)
Over the past twenty-five years the Duke history of economics faculty, together with the collection development librarians in the David M. Rubenstein Rare Book and Manuscript Library, have been gathering the papers of notable (mostly) twentieth century economists in what is now called The Economists Papers Project (EPP). Over time that archive has grown and become central to historical research on economics in the postwar period. The papers of Edwin Burmeister, Evsey Domar, Franklin Fisher, Duncan Foley, Lawrence Klein, Franco Modigliani, and Robert Solow, all MIT faculty or students, have attracted scholars from around the world. After Paul Samuelson's death in December 2009, his papers, by prior arrangement, came to the EPP and quickly became a magnet for historians of economics. In response, early in 2010 I was encouraged by my colleagues Kevin Hoover, Bruce Caldwell, Craufurd Goodwin, and Neil De Marchi to plan a conference in the History of Political Economy Annual Conference series to examine the history of MIT economics. After a year's worth of conversations and emails, I invited a number of individuals to consider a variety of projects exploring MIT's role in the transformation of American economics in the postwar period. That conference, held in April 2013 at the R. David Thomas Conference Center at Duke University, was sponsored as usual by the Duke University Press. However the very generous financial support of the Alfred P. Sloan Foundation made possible the expansion of the "standard" HOPE Conference into one that included a larger number of participants and papers. In the end the conferees learned that telling the story of MIT's role in the postwar period required attending to both the particular circumstances that shaped MIT and the various ways in which economics itself was changing.
Keywords: A1; A2; B2; B3; D00; E00; 330; MIT; Paul Samuelson; E. B. Wilson; Robert Solow; Graduate Education; historiography of economics